The Impact of Stress Due to Remote Working (Teleworking) Caused by Tecnostress on Employee Satisfaction, Anxiety, and Performance in DIY - Yuniar Yulfannada Yasiroh; Suhada (Pusat Riset dan Inovasi Nasional, 2025)
The advancement of information technology has significantly transformed work patterns, leading to the widespread adoption of remote work or teleworking. While teleworking offers flexibility and convenience, excessive use of technology can result in technostress, which can negatively impact employees' psychological well-being and job performance. This study aims to examine the effect of technostress on job satisfaction, anxiety, and performance among teleworkers in the Special Region of Yogyakarta (DIY). A quantitative approach utilizing Partial Least Square Structural Equation Modeling (PLS-SEM) was applied, with 100 respondents participating in the study. The results indicate that technostress has a negative effect on job satisfaction, suggesting that high levels of stress caused by technology usage in teleworking reduce employees' satisfaction with their jobs. Additionally, technostress has a positive effect on work-related anxiety, meaning that increased technostress leads to heightened anxiety levels among teleworkers. Anxiety, in turn, was found to negatively influence job satisfaction, highlighting the detrimental impact of anxiety on employees' contentment with their work. However, anxiety did not show a significant impact on performance, indicating that while anxiety affects satisfaction, it does not directly hinder job performance. On the other hand, job satisfaction has a significant positive effect on performance, meaning that employees who are more satisfied with their jobs tend to perform better. These findings emphasize the importance of managing technostress to maintain a productive and healthy digital work environment. Practical implications include the need for digital training to help employees manage technology effectively, psychological support to alleviate stress and anxiety, and the development of structured remote work policies that prioritize employee well-being. By addressing these factors, organizations can improve job satisfaction, reduce anxiety, and enhance overall performance in teleworking environments.